Examination of Indium Triphospholyls as Precursors for Nanoparticle Synthesis. Issue 11 (1st March 2021) - Rund, Reinhard; Bauer, Susanne; Stauber, Andreas; Seidl, Michael; Ojo, Wilfried‐Solo; Ferrari, Fabio; Chaudret, Bruno; Nayral, Céline; Delpech, Fabien; Scheer, Manfred
Abstract: The synthesis and characterization of the new compounds K(P3 C2 R2 ) [R=Ad (2 ), s Bu (3 )] and In(P3 C2 R2 ) [R=Ad (4 ), Mes (5 )] are described. Further, the synthesis of indium nanoparticles via a single‐source precursor approach using In(1, 2, 4‐P3 C2 t Bu2 ) (1 ) as precursor is reported. These nanoparticles were characterized by TEM, HRTEM, EDX, XRD, NMR, and optical spectroscopy. Abstract : New compounds of the type M(1, 2, 4‐P3 C2 R2 ) (M=K, In, R=Ad, s Bu, Mes) were synthesized, characterized, and examined in view of their use as precursors for indium‐based nanoparticles.